IDENTIFIKASI BIODIVERSITAS TANAMAN OBAT DIHUTAN SESAOT SEBAGAI BUKU SAKU MATA KULIAH BIODIVERSITAS RINJANI - Maulida Atrianingsih (Bioscientiae, 2026)
This study aims to identify the diversity of medicinal plants in Sesaot Village Forest, West Lombok Regency, and develop a pocket book as a learning resource for the Biodiversity Rinjani course. The research employs a descriptive-exploratory approach with qualitative methods, involving direct observation and in-depth interviews with local communities, including traditional healers (belian). The study identified 15 medicinal plant species from 12 families distributed across various orders. These plants have been traditionally used by the community for treating mild to moderate illnesses. For example, Orthosiphon aristatus (cat’s whiskers) is used for hypertension, Piper betle (betel leaf) for treating nosebleeds, and Zingiber officinale (ginger) for rheumatism and body warming. This utilization reflects a still-thriving and relevant ethnobotanical practice in rural communities. Medicinal plants were found both in the surrounding forest and home gardens, demonstrating sustainable use of local resources. Knowledge of these species and their uses has been passed down orally from generation to generation. To support the preservation of this knowledge while enhancing the effectiveness of learning, a pocket book was developed containing both scientific and local information: Latin names, local names, used plant parts, benefits, and usage methods. This book is practical, portable, and engaging for students to read at any time. Besides supporting contextual learning, it serves as a medium for conserving local knowledge and increasing awareness of biodiversity’s importance. Thus, this research contributes not only to higher education but also to the preservation of local culture and sustainable ecosystems.